2011
DOI: 10.1038/bjc.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome of oestrogen receptor-positive operable primary breast cancer in older women: a large series from a single centre

Abstract: Introduction:A Cochrane review of seven randomised trials (N=1571) comparing surgery and primary endocrine therapy (PET) (oestrogen receptor (ER) unselected) shows no difference in overall survival (OS). We report outcome of a large series with ER-positive (ER+) early invasive primary breast cancer.Methods:Between 1973 and 2009, 1065 older (⩾70 years) women (median age 78 years (70–99)) had either surgery (N=449) or PET (N=616) as initial treatment.Results:At 49-month median follow-up (longest 230 months), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
36
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 23 publications
6
36
1
Order By: Relevance
“…The overall outcome of the two age groups with TNBCs was poor with a 5-year breast cancer survival of 73% and 79% in <70 and ≥70 years age groups respectively, which is in keeping with the literature [30], as compared to that reported by us (5-year breast cancer survival being 91% and 90% respectively for the whole series of older women and in the ER positive subgroup) [12], [20]. However, despite the fact that they did not receive any adjuvant chemotherapy, the older women did not do any worse than their younger counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…The overall outcome of the two age groups with TNBCs was poor with a 5-year breast cancer survival of 73% and 79% in <70 and ≥70 years age groups respectively, which is in keeping with the literature [30], as compared to that reported by us (5-year breast cancer survival being 91% and 90% respectively for the whole series of older women and in the ER positive subgroup) [12], [20]. However, despite the fact that they did not receive any adjuvant chemotherapy, the older women did not do any worse than their younger counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…8 This survey confirms that AIs have also mostly replaced tamoxifen in the PET setup. Few papers confirming the efficacy of AIs as PET have been published [9][10][11] and AIs have not been compared with surgery in a prospective randomised fashion. One trial that attempted to do this closed early owing to poor recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective study of 616 PET patients, in which tamoxifen was used for the majority (69%) but an AI was used for others, with a median follow-up duration of 41 months, reported tumour progression in 45% of patients with a median time to progression of 49 months. 10 In another study of 101 patients treated with letrozole, with a median follow-up duration of 56 months, 18% of patients with hormone receptor positive tumours did not respond and another 18% responded initially but later progressed. 11 This makes PET even with an AI decidedly inferior to surgery in terms of local control.…”
Section: Discussionmentioning
confidence: 99%
“…19 Not only in the south of the Netherlands but also in other parts of Europe, a substantial number of elderly women with breast cancer are receiving PET. 5,20 Wyld et al reported 40% of the women C70 years were receiving PET for breast cancer in the UK in 2002. 5 We found large differences between hospitals in the percentage of elderly breast cancer patients treated with PET in the south of the Netherlands, indicating that there is a lack of consensus between physicians with respect to its use.…”
Section: Discussionmentioning
confidence: 99%